The Quality of Quail Eggs Sold in Various Traditional Markets in Kediri City, East Java, Indonesia - Anif Mukaromah Wati; Madyasta, Gistananda; Sa’ad, Wan Zuhainis; Aprylasari, Dede (Journal of Agriprecision & Social Impact, 2024)
This study aims to evaluate the quality of quail eggs sold in various traditional markets in Kediri City, East Java, Indonesia. The research was conducted from July to September 2024 at several traditional market locations, namely Mrican Market, Campurejo Market, Semen Market, Bandar Market, and Pahing Market. The quality parameters tested include the presence of Salmonella, Total Plate Count (TPC), pH, air cell depth, and shell thickness. The quality testing of quail eggs was carried out at PSDKU UB Kediri. The results of the study show that the quail eggs sold in these markets are safe for consumption, with no Salmonella contamination (0 cfu/ml) and TPC values within safe limits (2.1 x 10³ to 4.4 x 10³ cfu/ml). The pH values of the eggs range from 6.3 to 6.9, indicating good freshness. The air cell depth ranges from 1.54 mm to 2.36 mm, and the shell thickness ranges from 0.19 mm to 0.20 mm, indicating good and consistent physical quality of the eggs. Overall, the quality of quail eggs in the traditional markets of Kediri City can be categorized as good based on the parameters tested.